Prevalence and sociodemographic factors responsible for anaemia in pregnancy: experience in a military hospital in Bangladesh - Alam, Fakhrul; Khanum, Shakila; Jahan, Israt; Ahmed, Jamal Uddin (BIRDEM Medical Journal, 2020)
Background: Anemia during pregnancy is associated with adverse outcomes. Prevalence of anemia is thought to be high in developing countries. This study was aimed at determining the prevalence and socio-demographic and reproductive factors associated with anemia among a group of pregnant mother. Methods: This cross-sectional observational study was conducted on pregnant women who visited the antenatal clinic of Combined Military Hospital (CMH), Savar, Dhaka from January 2017 to December 2019. Hemoglobin level was measured in all these women to assess the presence of anemia and was categorized according to the World Health Organization (WHO) criteria. Demographic data and information on maternal age, gestational age, educational and income level, and socioeconomic status were collected from anemic pregnant women and were analyzed. Results: Out of 1500 pregnant women 525 (35%) were found to be anemic (Hemoglobin <11.0 g/dl). Among the 525 anemic women, 347 (66.1%) had mild anemia, 157 (29.9%) had moderate anemia and 21 (4.0%) women had severe anemia. Majority (48%) of the anemic women were less than 25 years old and majority (47%) had body mass index (BMI) <18.5 kg/m2. Most of the women (58%) presented in their second trimester of pregnancy. More than two thirds pregnant women were multigravida. More than 50% women had history of abortion and around one third had 2 or more abortions. Most of the women (56%) reported another pregnancy within 24 months of current pregnancy. Sixty four percent of the patients completed secondary education, 75% were homemaker and 56% lived in rural area. Most of the patients (80%) had a family income per month less than 20000 taka. Majority (58.4%) of the women did not receive any iron supplementation during this pregnancy. Conclusions: This study results show that more than one third of the pregnant women suffer from anemia irrespective of gestational week, but is more common in those presenting in second trimester of pregnancy, those who are younger, lean and thin, having history of previous pregnancy and bad obstetric history. Birdem Med J 2021; 11(1): 52-56